Management of Accidental Uterine Rupture in a Pregnant Goat - Singh, Nikita; Kumar, Rajesh; Verma, Hukum Chandra; Singh, Bhoopendra; Sachan, Nikhil (The Indian Journal of Animal Reproduction, 2025)
A doe in its advanced gestation was brought to the Veterinary Clinical Complex, ANDUAT, UP, after being met with a roadside accident that resulted in uterine rupture. Considering the animal to be critical, an emergency caesarean section was performed. Resultant of the surgical celiotomy, the doe delivered two fetuses, out of which only one survived.